2013
DOI: 10.1007/s00418-013-1135-4
|View full text |Cite
|
Sign up to set email alerts
|

RNA-binding protein RBM8A (Y14) and MAGOH localize to centrosome in human A549 cells

Abstract: RBM8A (Y14) is carrying RNA-binding motif and forms the tight heterodimer with MAGOH. The heterodimer is known to be a member of exon junction complex on exporting mRNA and is required for mRNA metabolisms such as splicing, mRNA export and nonsense-mediated mRNA decay. Almost all RBM8A-MAGOH complexes localize in nucleoplasm and shuttle between nuclei and cytoplasm for RNA metabolism. Recently, the abnormality of G2/M transition and aberrant centrosome regulation in RBM8A- or MAGOH-deficient cells has been rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 45 publications
3
25
0
Order By: Relevance
“…Moreover, a putative RNA-binding protein called SZY-20 has been claimed to traffic to centrosomes and plays a critical role in limiting centrosome size in C. elegans [32]. Interestingly, the RNA-binding protein RBM8A, known to be required for mRNA metabolic processes such as splicing, mRNA export and nonsense-mediated mRNA decay, is localized to the centrosome and nuclei [33]. These data suggest that centrosomal and ciliary functions may be associated with mRNA transport and splicing, thus supporting our observations.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a putative RNA-binding protein called SZY-20 has been claimed to traffic to centrosomes and plays a critical role in limiting centrosome size in C. elegans [32]. Interestingly, the RNA-binding protein RBM8A, known to be required for mRNA metabolic processes such as splicing, mRNA export and nonsense-mediated mRNA decay, is localized to the centrosome and nuclei [33]. These data suggest that centrosomal and ciliary functions may be associated with mRNA transport and splicing, thus supporting our observations.…”
Section: Resultsmentioning
confidence: 99%
“…Our data indicate Magoh can influence microtubules indirectly, by modulating expression of key microtubule/mitosis regulatory proteins. However, Magoh may also directly influence microtubule organization; it localizes to the mitotic spindle (Ishigaki et al, 2013), was identified in proteomic studies as a mitotic spindle component (Bonner et al, 2011; Sauer, 2004), and physically associates with the microtubule-associated protein MAP1B (Tretyakova, 2005). It will be interesting to assess if Magoh’s RNA binding function is necessary for microtubule regulation and if so to identify its RNA cargos specifically at M phase.…”
Section: Discussionmentioning
confidence: 99%
“…HeLa and A549 are most popularly used and well documented cell lines, from our previous studies, we have clearly understood the biogenesis of RBM8A and Upf2 in HeLa and A549 (Ishigaki et al, ; Ishigaki et al, ; Ishigaki, Nakamura, Tatsuno, Ma, & Tomosugi, ; Tatsuno & Ishigaki, ; Tatsuno, Nakamura, Ma, Tomosugi & Ishigaki, ). We performed immunostaining for Y14 and Upf2 in an ultrathin section for TEM as shown in Figure .…”
Section: Resultsmentioning
confidence: 82%
“…Images provided by conventional TEM were shown in supporting information. Y14 is a member of the EJC and localize to perispeckles that is the place for mRNA processing (Ishigaki et al, 2013;Ishigaki et al, 2014). In the cells, the phosphorylation of Y14 is observed and its roles in mRNA processing have been proposed (Chuang, Peng, & Tarn, 2011;Ishigaki et al, 2015;Tatsuno & Ishigaki, 2018).…”
Section: Immunoelectron Microscopy With Postembeddingmentioning
confidence: 99%